Structural adaptation and heterogeneity of normal and tumor microvascular networks. - Axel R Pries; Annemiek J M Cornelissen; Anoek A Sloot; Marlene Hinkeldey; Matthew R Dreher; Michael Höpfner; Mark W Dewhirst; Timothy W Secomb (PLoS Computational Biology, 2009)
Relative to normal tissues, tumor microcirculation exhibits high structural and functional heterogeneity leading to hypoxic regions and impairing treatment efficacy. Here, computational simulations of blood vessel structural adaptation are used to explore the hypothesis that abnormal adaptive responses to local hemodynamic and metabolic stimuli contribute to aberrant morphological and hemodynamic characteristics of tumor microcirculation. Topology, vascular diameter, length, and red blood cell velocity of normal mesenteric and tumor vascular networks were recorded by intravital microscopy. Computational models were used to estimate hemodynamics and oxygen distribution and to simulate vascular diameter adaptation in response to hemodynamic, metabolic and conducted stimuli. The assumed sensitivity to hemodynamic and conducted signals, the vascular growth tendency, and the random variability of vascular responses were altered to simulate 'normal' and 'tumor' adaptation modes. The heterogeneous properties of vascular networks were characterized by diameter mismatch at vascular branch points (d(3) (var)) and deficit of oxygen delivery relative to demand (O(2def)). In the tumor, d(3) (var) and O(2def) were higher (0.404 and 0.182) than in normal networks (0.278 and 0.099). Simulated remodeling of the tumor network with 'normal' parameters gave low values (0.288 and 0.099). Conversely, normal networks attained tumor-like characteristics (0.41 and 0.179) upon adaptation with 'tumor' parameters, including low conducted sensitivity, increased growth tendency, and elevated random biological variability. It is concluded that the deviant properties of tumor microcirculation may result largely from defective structural adaptation, including strongly reduced responses to conducted stimuli.